Assaying progesterone, estradiol and cortisol concentrations in hair of Père David deer hinds: an alternative way to reflect seasonality of steroid secretion. Issue 3 (4th May 2018) - Ping, Xiaoge; Liu, Ni; Jiang, Zhigang; Xu, Huailiang; Bai, Jiade; Zhang, Shumiao; Zhong, Zhenyu; Li, Chunwang
Abstract: The use of a hair hormone concentration assay is increasingly recognized as a useful and noninvasive technique for monitoring the endocrinological status of animals. However, few studies have focused on reproductive and stress hormones together. We used a chemiluminescent immunoassay to determine whether the progesterone, estradiol, and cortisol concentrations could be measured from hair and whether these hormone concentrations varied in different hair segments of captive Père David deer hinds. We found that progesterone, estradiol, and cortisol could be measured in the hair samples and that the progesterone concentration varied but the estradiol and cortisol concentrations did not among different hair segments. Contrary to the segmental decline in hair cortisol found in many studies, we found that progesterone concentration was higher near the tip than at the base of hair in Père David deer. This suggests that the variation in segmental hair steroid hormone concentration in seasonal molting animals may be mainly due to internal reproductive cycles and that hair steroid hormones may reflect long-term physiological changes and can thus be used for the conservation and management of wildlife.